2017
DOI: 10.1016/j.cortex.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers later diagnosed with autism exhibit multiple structural abnormalities in temporal corpus callosum fibers

Abstract: Interhemispheric functional connectivity abnormalities are often reported in autism and it is thus not surprising that structural defects of the corpus callosum (CC) are consistently found using both traditional MRI and DTI techniques. Past DTI studies however, have subdivided the CC into 2 or 3 segments without regard for where fibers may project to within the cortex, thus placing limitations on our ability to understand the nature, timing and neurobehavioral impact of early CC abnormalities in autism. Levera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 98 publications
3
17
0
Order By: Relevance
“…These findings are complemented by a smaller study of community identified 1 year to 4 year old children with ASD who had atypical development of white matter ultrastructure relative to typically developing controls, particularly in the frontal tracts86 and within the corpus callosum in those younger than 30 months 87…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 91%
“…These findings are complemented by a smaller study of community identified 1 year to 4 year old children with ASD who had atypical development of white matter ultrastructure relative to typically developing controls, particularly in the frontal tracts86 and within the corpus callosum in those younger than 30 months 87…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 91%
“…Despite evidence from lesion studies and volumetric analyses that highlight the importance of the amygdala in ASD, to the best of our knowledge, no study has investigated amygdala connectivity directly in ASD. A number of previous studies of ASD have investigated microstructural differences in WM pathways that connect to temporal lobe structures: in young children with ASD, elevated FA has been identified in temporal lobe projections (Fingher et al, ) and the uncinate fasciculus, which links the temporal and frontal lobes (Solso et al, ), and reduced diffusivity reported in corpus callosum projections that link the temporal lobe with the occipital lobe (Fingher et al, ). Conversely in older children with ASD, significantly reduced FA has been reported in WM surrounding the amygdala (Noriuchi et al, ) and in the inferior longitudinal fasciculus (ILF) and the inferior fronto‐occipital fasciculus (IFOF) (both of which connect temporal lobe structures, including the amygdala) (Jou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, it remains to be established whether Cntnap2 disruption may cause neurodevelopmental deficits through disruption of axonal action potential dynamics or aberrant brain myelination. Their study is of importance to gain understanding of reduced white matter integrity and conductivity implicated in neurodevelopmental disorders (Vissers et al 2012;Rane et al 2015;Wolff et al 2015;Fingher et al 2017).…”
mentioning
confidence: 99%